2023
DOI: 10.3390/ijms24087182
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a (E)-β-Ocimene Synthase Gene Contributing to the Defense against Spodoptera litura

Abstract: Soybean is a worldwide crop that offers valuable proteins, fatty acids, and phytonutrients to humans but is always damaged by insect pests or pathogens. Plants have captured sophisticated defense mechanisms in resisting the attack of insects and pathogens. How to protect soybean in an environment- or human-friendly way or how to develop plant-based pest control is a hotpot. Herbivore-induced plant volatiles that are released by multiple plant species have been assessed in multi-systems against various insects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 78 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…It is well-known that seeds contain everything necessary for the new life development, and the results of this research underscore the significance of byproducts as novel raw materials and the importance of investing in processes for extracting, isolating, or applying their beneficial components. Due to its protective function in plants, pepper byproducts (seeds, pepper seed oil) represent a potential source of this terpene to be used as a biopesticide, as indicated by published studies (Kang et al, 2018;Han et al, 2023). Biopesticides are gaining significant attention globally due to their potential to replace synthetic pesticides that harm the environment (Nuruzzaman et al, 2019;Meshram et al, 2022;Koul, 2023).…”
Section: Smoke Point Of Cold-pressed Sweet Pepper Seed Oil: Compariso...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that seeds contain everything necessary for the new life development, and the results of this research underscore the significance of byproducts as novel raw materials and the importance of investing in processes for extracting, isolating, or applying their beneficial components. Due to its protective function in plants, pepper byproducts (seeds, pepper seed oil) represent a potential source of this terpene to be used as a biopesticide, as indicated by published studies (Kang et al, 2018;Han et al, 2023). Biopesticides are gaining significant attention globally due to their potential to replace synthetic pesticides that harm the environment (Nuruzzaman et al, 2019;Meshram et al, 2022;Koul, 2023).…”
Section: Smoke Point Of Cold-pressed Sweet Pepper Seed Oil: Compariso...mentioning
confidence: 99%
“…Researchers, including Kang and colleagues, have demonstrated that treating Chinese cabbage with β-ocimene can activate protection against green peach aphids (Myzus persicae), making it an interesting approach for natural pest control in agriculture. Since the cloning of the first gene (E)-β-ocimene synthase (AtTPS03) from Arabidopsis (a plant from the Brassicaceae family), more genes responsible for the synthesis of (E)-ocimene and their insect-repellent functions have been characterized in various plants, such as tomatoes, Chinese cabbage, and lima beans, soyabean and tobacco (Kang et al, 2018;Han et al, 2023). For culinary use of oils, several factors are essential, including the content of free fatty acids, water, peroxide value, saponification value, iodine number, fatty acid composition, and other components.…”
Section: Introduction mentioning
confidence: 99%
“…As an example, 2-PE mediates both direct and indirect plant defenses, as well as attracting pollinators such as beetles, bees, and butterflies [49]. Terpenes such as β-caryophyllene play roles in mutualistic interactions, plant defense, and insect attraction [50][51][52]. Geraniol, an acyclic monoterpene, possesses anti-microbial, antifeedant, and insect repellant activities [53].…”
Section: P Lactiflora CV Zifengyu Is a Good Candidate For Extracting ...mentioning
confidence: 99%
“…Direct deprotonation results in the formation of an acyclic monoterpene hydrocarbon [e.g., β‐myrcene, ( Z )‐β‐ocimene or ( E )‐β‐ocimene], while water capture with subsequent deprotonation leads to the formation of acyclic alcohol [geraniol, nerol, (−)‐(3 R )‐linalool, or (+)‐(3 S )‐linalool] (Figure 3, inset 1). MTSs that produce one of these acyclic monoterpenes preferentially have been characterized across the angiosperm lineage (Abbas et al., 2019; Aharoni et al., 2004; Arimura et al., 2004, 2008; Aros et al., 2012; Ashaari et al., 2020; Bin et al., 2023; Bohlmann et al., 2000; Booth et al., 2017; Cao et al., 2014; Chen et al., 2003, 2010, 2018, 2023; Dudareva et al., 1996, 2003; Fäldt et al., 2003; Fan et al., 2023; Gao et al., 2018; Günnewich et al., 2007; Han et al., 2023; Hosoi et al., 2004; Huang et al., 2018, 2021, 2022; Ibdah et al., 2022; Iijima, Davidovich‐Rikanati, et al., 2004; Iijima, Gang, et al., 2004; Ito & Honda, 2007; Javedan Asl et al., 2015; Jia et al., 1999; Jing‐Jing et al., 2014; Magnard et al., 2018; Masumoto et al., 2010; Mei et al., 2017; Nagegowda et al., 2008; Nawade et al., 2020; Önder et al., 2021; Ruan et al., 2016; Shimada et al., 2004, 2005; Sugiura et al., 2011; van Schie et al., 2007; Wang & Ito, 2014; Yahyaa et al., 2015; Yang et al., 2005, 2013; Yuan et al., 2008; Yue et al., 2014; Zager et al., 2019; Zeng et al., 2016; Zhang et al., …”
Section: Establishing the Reaction Sequencementioning
confidence: 99%